Retaining Life Tenure: The Case for a “Golden Parachute” - David R. Stras; Ryan W. Scott (Washington University Law Quarterly, 2005)
The first vacancies on the Supreme Court in eleven years have sparked renewed debate about the continued viability of life tenure for federal judges. Scholars have decried life tenure as one of the Framers' worst blunders, pointing to issues such as strategic retirement, longer average tenure, and widespread mental infirmity of Justices. In this Article, the authors argue that, notwithstanding the serious problem of mental and physical infirmity on the Court, life tenure should be retained. They also argue that recent statutory proposals to eliminate or undermine life tenure, for example through a mandatory retirement age or term limits, are unconstitutional. Surprisingly, scholars have failed to take a multidisciplinary approach to the question of life tenure, or to propose alternatives that address its weaknesses without abolishing it. The authors address that gap by adopting an incentives approach to Supreme Court retirement. They first demonstrate that, as an historical and empirical matter, pensions have been the most important factor in influencing the retirement timing of Supreme Court Justices and comparable actors over history. Building on that track record, the authors propose that Congress create a “golden parachute” for Supreme Court Justices by doubling their retirement benefits upon reaching an appropriate retirement age or upon certifying a mental or physical disability. They also propose modest institutional reforms that will make the office of “Senior Justice” more attractive to Justices considering retirement.
Keywords: Federal judges – Retirement; Retirement; Supreme Court justices (United States); Supreme Court justices (United States) – Retirement; Judges – Selection & amp; appointment; Golden parachutes (Executive compensation); Judge tenure; Mandatory retirement; Retirement age; Retirement benefits; United States